c-Rel Is the Pivotal NF-κB Subunit in Germinal Center Diffuse Large B-Cell Lymphoma: A LYSA Study - Faumont, Nathalie; Taoui, Oussama; Collares, Davi; Jais, Jean-Philippe; Leroy, Karen; Prévaud, Léa; Jardin, Fabrice; Molina, Thierry J.; Copie-Bergman, Christiane; Petit, Barbara; Gourin, Marie-Pierre; Bordessoule, Dominique; et al. (Frontiers in Oncology, 2021)
The REL locus is frequently amplified in diffuse large B-cell lymphomas (DLBCLs) of the Germinal Center B-cell subtype (GCB-DLBCLs). But relationships between the c-Rel NF-kappa B subunit and GCB-DLBCLs remain unclear. Here, we found that strong c-Rel DNA-binding activity was mostly found in GCBs on two independent series of 48 DLBCLs and 66 DLBCLs, the latter issued from the GHEDI series. c-Rel DNA-binding activity was associated with increased REL mRNA expression. Extending the study to the whole GHEDI and Lenz DLBCL published series of 202 and 233 cases, it was found that the c-Rel gene expression profile (GEP) overlapped partially (12%) but only with the GCB GEP and not with the GEP of ABC-DLBCLs. Exhibiting a better overall survival, cases with both overexpression of REL mRNA and c-Rel GEP were GCBs in 88% and 83% of the GHEDI or Lenz’s DLBCL series respectively. These cases were associated with various recurrent GCB-DLBCLs genetic events, including REL gains, BCL2 translocation, MEF2B, EZH2, CREBBP, and TNFRSF14 mutations and with the EZB GCB genetic subtype. Functionally, overexpression of c-Rel induced its constitutive nuclear localization and protected cells against apoptosis while its repression tended to increase cell death. These results show that, clinically and biologically, c-Rel is the pivotal NF-kappa B subunit in the GCB-DLBCL subgroup. Functionally, c-Rel overexpression could directly promote DLBCL tumorigenesis without need for further activation signals.